INTERPRETING THE QURAN'S PERSPECTIVE ON HATE SPEECH THROUGH FAZLUR RAHMAN'S DOUBLE MOVEMENT THEORY - Bahri, Samsul; Simangunsong, Ali Abdurahman (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
This article examines how to respond and deal with hate speech through two verses of the Quran, namely al-Ḥujurāt (49:11) and al-Anʿām (6:108). The widespread dissemination of hate speech across various platforms has raised concerns. This activity not only has the potential to incite discriminatory behavior and provoke violence, but the larger issue at hand is the threat of national disintegration and social disharmony. Therefore, using Fazlur Rahman's double movement method, a socio-historical contextual analysis of the period during which these verses were revealed is conducted to uncover the moral message of the Quran and contextualize it for the present day. The results of this study indicate that Surah Al-Ḥujurāt (49:11) and Surah al-Anʿām (6:108) emphasize the importance of promoting politeness and respect in communication, by refraining from using derogatory titles or nicknames that may demean or offend others. It also stresses the importance of self-control to avoid engaging in spreading hate speech, both in verbal and online interactions. Additionally, responsible use of social media is highlighted, prioritizing healthy discussions and dialogues to prevent online conflicts that could disrupt societal harmony.